Synthesis, structure, characterization, and multifunctional properties of a family of rare earth organic frameworks. Issue 15 (30th March 2017) - Li, Haoran; Sheng, Tianlu; Xue, Zhenzhen; Zhu, Xiaoquan; Hu, Shengmin; Wen, Yuehong; Fu, Ruibiao; Zhuo, Chao; Wu, Xintao
Abstract : A series of isomorphic 3D layered rare earth hydroxide frameworks RE3 (OH)7 (1, 5-NDS) 1, 5-NDS = 1, 5-naphthalenedisulfonate) with high stability, coordinated ions tuning fluorescence and large magnetic susceptibilities was reported. Abstract : A series of isomorphic 3D layered rare earth hydroxide (LREH) frameworks RE3 (OH)7 (1, 5-NDS) (RE = Y (1 ), Gd (2 ), Er (3 ), Yb (4 ); 1, 5-NDS = 1, 5-naphthalenedisulfonate) has been synthesized under hydrothermal conditions. The crystal structures, thermal stabilities, photoluminescence, and magnetic properties of these compounds have been investigated. The results demonstrate that the compounds are highly stable even at 351 °C and emit strong purple fluorescence, whose colour can be tuned by the coordinated rare earth ions. Their magnetic susceptibilities have also been measured, leading the compounds to be promising multifunctional materials.